The The Social Role of Kader Surabaya Hebat in Addressing Stunting in Surabaya City: A Sociological Review - Septi Ariadi; Nur Syamsiyah; Rafi Aufa Mawardi; Pingkan Sekar Savira; Rani Sukma Ayu Suteja (CV. Era Digital Nusantara, 2026)
Abstract: Stunting remains a serious public health issue in Indonesia and requires collaboration across sectors and community participation. This study examines how the Kader Surabaya Hebat (KSH) view stunting and how they implement their social roles in preventing stunting and early signs of growth failure among children in Surabaya. Purpose: This study analyzes KSH empowerment to strengthen social roles in addressing stunting in Surabaya City. Design/Methodology/Approach: This study used an explanatory sequential design for the mixed-methods approach. It started with a survey of the cadres, with 50 participating, focusing on their knowledge, attitudes, and practices. It was followed by a Focus Group Discussion, during which eight participants were invited. To provide a broader context for the survey results, the study employed an FGD. The survey results show that the cadres have good knowledge of stunting, including nutritional status, monitoring growth, and feeding practices. The qualitative findings also show that KSH play various roles, including educating, accessing, advocating, and rallying the community. Findings: The study results indicate that the KSH play significant roles within the community, contributing to the cadres’ good knowledge. Furthermore, the study suggests that their skills need improvement, better coordination across sectors, and greater support to enable them to contribute more to the Surabaya administration’s stunting prevention initiatives. Originality/value: This study contributes to examining how the Kader Surabaya Hebatuse social capital addresses stunting.